Electromagnetic simulation of amorphous silicon waveguides - Lourenço, Paulo (2018)
In the past several decades, the Finite-Difference Time-Domain (FDTD) method has become one of the most powerful numerical techniques in solving the Maxwell’s curl equations and has been widely applied to solve complex optical and photonic problems. This method divides space and time into a regular grid and simulates the time evolution of Maxwell’s equations. This paper reports some results, obtained by a set of FDTD simulations, about the characteristics of amorphous silicon waveguides embedded in a SiO2 cladding. Light absorption dependence on the material properties and waveguide curvature radius are analysed for wavelengths in the infrared spectrum. Wavelength transmission efficiency is determined analysing the decay of the light power along the waveguides and the obtained results show that total losses should remain within acceptable limits when considering curvature radius as small as 3 μm at its most.